THE ROLE OF FATAYAT NU IN COUNTERING SEXTORTION AND PROTECTING WOMEN’S DIGNITY: A QUALITATIVE STUDY OF URBAN MUSLIM SOCIETY - Indriyani Idris; Galuh Aulia Ramadhanti; Kurniawan Kurniawan; Saima Arzeen (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2026)
This study examines sextortion as a form of gender-based sexual corruption within urban Muslim communities, particularly in educational and religious settings, and analyses the role of Fatayat Nahdlatul Ulama (NU) in addressing the culture of silence surrounding the issue. The research employed a qualitative design within an interpretive-critical paradigm. Data were collected through in-depth interviews with ten informants comprising educators, Fatayat NU cadres, urban community members, and students, as well as participant observation and document analysis. The data were analysed using thematic analysis informed by Feminist Standpoint Theory, the Spiral of Silence, social constructionism, and critical communication perspectives. The findings indicate three main themes. First, sextortion is frequently normalised through symbolic authority, moral legitimacy, and ambiguous social relations that obscure coercive practices. Second, fear of stigma, institutional reputation, and digital exposure reinforces a culture of silence, particularly among women in urban religious environments. Third, participatory communication spaces facilitated by Fatayat NU contribute to developing critical awareness and provide alternative forums for articulating women’s experiences, although these initiatives remain limited by uneven institutional support and the absence of integrated protection mechanisms. This study contributes to discussions on gendered corruption and urban Muslim communication by highlighting the relationship between patriarchal power relations, silence, and participatory religious activism in the prevention of sextortion.